The Effectiveness of Using the Quizalize Platform in Mastering Reading Comprehension among Ninth-Grade Students at Binjai Tigo Nagari Private Junior High School, Pasaman: فعالية استخدام منصة Quizalize في إتقان فهم المقروء لدى طلاب الصف التاسعفي المدرسة المتوسطة الأهلية بنجاي تيجو ناجاري باسامان - Nursi Nuraini; Eka Rizal (Institut Muslim Cendekia, 2026)
This study was motivated by the low reading comprehension ability of ninth-grade students at Binjai Tigo Nagari Private Junior High School, Pasaman, particularly due to difficulties in vocabulary mastery and low learning motivation caused by the limited use of interactive learning media and the lack of variation in teaching strategies for reading skills. This study aimed to investigate the effectiveness of the Quizalize platform in improving students’ reading comprehension skills. The study employed a quantitative approach using a quasi-experimental method with a Non-equivalent Control Group Design. The population consisted of all 28 ninth-grade students, who were divided into an experimental group and a control group. Data were collected through observation, tests, and documentation, and were analyzed using the Independent Sample t-test with the assistance of IBM SPSS Statistics 25. The findings revealed a statistically significant difference between the two groups, as the mean score of the experimental group increased from 31.66 in the pre-test to 61.66 in the post-test. The significance value obtained was 0.015, which was lower than 0.05, indicating that the use of the Quizalize platform was effective in enhancing students’ reading comprehension skills. Furthermore, the average N-Gain score of 0.43 indicated that the level of effectiveness was categorized as moderate. These findings highlight the importance of integrating interactive digital media into Arabic language learning, particularly in reading instruction, in order to improve students’ motivation and learning outcomes.